OPTIMALISASI PEMBERDAYAAN PROGRAM K3 (KEAGAMAAN, KESEHATAN DAN KEPENDIDIKAN) DI DESA RANTAU LANGKAP - Tri Wiyoko; Abdulah Abdulah; Subhanadri Subhanadri; Randi Eka Putra; Jusri Hartini (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
Online learning has had a low impact on children's reading interest and literacy in Rantau Langkap Village. Then the lack of sports activities in the afternoon which doesn't do much walking. As well as the problems found in Rantau Langkap Village, namely the medicinal plant garden program (Toga) in the yards of residents' homes. Community service activities are carried out in the village of Rantau Langkap, Tebo Ulu District, Tebo Regency, Jambi Province. The method for implementing this service is using service learning community service activities in March 2023. The results of community service activities show that; Religious activities are carried out by teaching reading the Koran in accordance with recitation and reciting both iqra' and juz amma in early childhood up to elementary school children. Tutoring activities are carried out by helping students in the Rantau Langkap village to have increasing writing, numeracy, and reading skills. In addition, it improves students' intellectual abilities, insight, motivation, and creativity. Health activities that have been carried out by reviving the sports sector so that they maintain health and can strengthen friendships between youth and women in Rantau Langkap Village.